Multi-Criteria Hypervisor Selection Using Analytic Hierarchy Process with Ex-Post Evaluation - Ronaldo Agung Nugroho; Dana Indra Sensuse; Sofian Lusa (Universitas Bumigora, 2026)
reassessment of virtualization platform selection in banking Information Technology environments. The objective of this study is to develop a structured, scalable decision-making model to determine the most appropriate hypervisor platform based on technical and non-technical criteria. The research method used is the Analytic Hierarchy Process, developed from qualitative coding of expert interview results and validated through pairwise comparisons by internal infrastructure specialists. The analysis includes consistency measurements, sensitivity analyses, and an ex-post evaluation by comparing analytical ranking results with actual organizational decisions. The results show that technical criteria dominate the decision process, accounting for 64.10% of the total decision weight. At the alternative level, the final priority weights are 45.40–45.44% for Alternative 1, 38.00% for Alternative 2, and 16.55–16.60% for Alternative 3, with Alternative 1 identified as the most optimal choice. Notably, the proposed model achieves a 100% alignment between the analytical ranking and the actual organizational decision, representing a substantial improvement over prior studies, which were largely confined to ex-ante evaluations and lacked empirical validation of decision outcomes. The conclusion of this study confirms that integrating ex-post evaluation into a multi-criteria decision analysis approach enhances the validity of the results and demonstrates a strong fit between the analytical model and real-world decision-making in the context of banking information technology infrastructure.